Do people walk more in transit-accessible places? - Yunkyung Choi; Subhrajit Guhathakurta (Journal of Transport and Land Use, 2020)
While transit-oriented developments (TODs) are generally believed to promote the use of sustainable travel modes, the degree to which various components of TODs influence travel behavior is still debatable. This paper revisits Chatman’s (2013) question: “Does TOD need the T?” by addressing the effect of rail transit access in influencing walking behavior in TOD areas. In particular, we compare TODs to other similar areas, with rail transit access being the key variable, and examine whether people are more likely to walk in TODs for purposes other than transit use. This hypothesis is tested using traffic analysis zones (TAZs) in the Atlanta Metropolitan Region. First, we identify TAZs within rail catchment areas and use propensity scores to match them with other TAZs with similar built environmental characteristics except for rail transit access. We then conduct a statistical analysis comparing walking trips for both commuting and non-commuting trips in these two TAZ groups. Our results confirm that the likelihood of walking trips increases in transit-accessible TAZs compared to other similar areas without transit. Therefore, states and localities can maximize the benefits of pedestrian-friendly built environments by making rail transit access an important part of their planning and design.